Transnational Identity in Thapa’s Seasons of Flight - Bhattarai, Punya Prasad (Adhyayan Journal, 2022)
This article focuses on the transnational identity of Nepali immigrants in America through the representative character of Prema in Manjushree Thapa’s novel, Season of Flight. The finding of the article is that transnational identity of immigrants is unstable and fluid. This instability and fluidity result in crossing the border from one nation to the next. Transnationalism is the process of globalization where immigrant adopts foreign culture and retains the roots simultaneously. Although immigrant has to undergo alienation and frustration in the host land, he/she prefers to live there because of immense freedom and liberty. The researcher has focused on the cultural aspect of immigrants living in transnational space, and hybridity as a theory has been applied to interpret and analyze the text.